The Great Northwestern R.R.; on verso: "Mrs. Bliss wasn't sure this was in Fair-Engine is to [sic] early" (1901)
The Great Northwestern R.R.; on verso: "Mrs. Bliss wasn't sure this was in Fair-Engine is to [sic] early".